2004
DOI: 10.1070/qe2004v034n03abeh002617
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic quasi-phase matching in nonlinear-optical crystals with an irregular domain structure

Abstract: We show the existence of a new class of astrophysical objects where the self-gravity of the dust is balanced by the force arising from shielded electric fields on the charged dust. The problem of equilibrium dust clouds is formulated in terms of an equation of hydrostatic force balance together with an equation of state. Because of the dust charge reduction at high dust density, the adiabatic index reduces from two to zero. This gives rise to a mass limit M AS for the maximum dust mass that can be supported ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 4 publications
3
4
0
Order By: Relevance
“…An important result of this section is that nonlinear wave-mixing effects seem to be promoted by the randomness of such systems. Similar conclusions for three-wave mixing in random nonlinear materials have been reported in the past [35,36] and more recently [37][38][39][40]. Such studies reported that phase-matching conditions, which can be difficult to achieve in pure and homogeneous materials, can be met more easily in a random structure although conditions are not optimized.…”
Section: Nonlinear Wave-mixingsupporting
confidence: 82%
“…An important result of this section is that nonlinear wave-mixing effects seem to be promoted by the randomness of such systems. Similar conclusions for three-wave mixing in random nonlinear materials have been reported in the past [35,36] and more recently [37][38][39][40]. Such studies reported that phase-matching conditions, which can be difficult to achieve in pure and homogeneous materials, can be met more easily in a random structure although conditions are not optimized.…”
Section: Nonlinear Wave-mixingsupporting
confidence: 82%
“…Numerical simulations were also used by Vidal and Martorell [34] to study the diffusive character of the second harmonic generated in random 1D crystal. These simulations also confirmed the well known analytical results that the disorder-induced loss of phase correlation leads to the emitted signal growing linearly with propagation distance [35,36]. In their recent work Bravo-Abad et al suggested that light scattering by randomly distributed ferroelectric domains might contribute towards appearance of forward emission peak of the second harmonic signal [37].…”
Section: Fig 2 (Color Online)supporting
confidence: 83%
“…While, strictly speaking, the case considered here is two-dimensional, it turns out that even the simple 1D theory already provides a fairly good agreement with the experimental results. Following [12] and the discussions by Morozov and Chirkin [13] and Dolino [14] one can show that the intensity of the SH wave generated in a medium with random distribution of ferroelectric domains is given by…”
Section: Theoretical Model and Discussionmentioning
confidence: 99%